2010
DOI: 10.1371/journal.pone.0015410
|View full text |Cite
|
Sign up to set email alerts
|

Apolipophorin-III Mediates Antiplasmodial Epithelial Responses in Anopheles gambiae (G3) Mosquitoes

Abstract: BackgroundApolipophorin-III (ApoLp-III) is known to play an important role in lipid transport and innate immunity in lepidopteran insects. However, there is no evidence of involvement of ApoLp-IIIs in the immune responses of dipteran insects such as Drosophila and mosquitoes.Methodology/Principal FindingsWe report the molecular and functional characterization of An. gambiae apolipophorin-III (AgApoLp-III). Mosquito ApoLp-IIIs have diverged extensively from those of lepidopteran insects; however, the predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 37 publications
2
38
1
Order By: Relevance
“…In particular, a number of proteins with known immune function were reduced in expression ( Table 1). Spot 3 showed homology to apolipophorin, which functions in the hemolymph to transport lipids and aids in the commencement of the innate immune response, 19 and its expression was reduced by approximately 50% in hemolymph from starved larvae. Arylphorin (spot number 4) was downregulated by 37% in the hemolymph of starved larvae.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a number of proteins with known immune function were reduced in expression ( Table 1). Spot 3 showed homology to apolipophorin, which functions in the hemolymph to transport lipids and aids in the commencement of the innate immune response, 19 and its expression was reduced by approximately 50% in hemolymph from starved larvae. Arylphorin (spot number 4) was downregulated by 37% in the hemolymph of starved larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Apolipophorins are proteins that bind lipids to form lipoproteins. Insect apolipophorin-III has been implicated in both detoxification of LPS and as a pattern recognition receptor in immune responses (Whitten et al, 2004), and has been shown to mediate anti-plasmodial epithelial responses in Anopheles gambiae (G3) mosquitoes (Gupta et al, 2010). Similarly, long chain fatty acid ligase and proprotein convertase subtilisin were down-regulated in response to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…SBC3 does not provoke an enhanced immune response as indicated by the lack of an increase in the haemocyte density and the expression of antimicrobial and immune related peptides. A number of proteins were shown to decrease in abundance in larvae that received SBC3 and these included carboxylesterase (spot 3, Table 1) which has physiological functions in neurotransmitter degradation, hormone and pheromones specific metabolism, detoxification, defense and behavior (Vogt et al 1985;Taylor and Radic 1994), 27 kDa haemolymph protein (spot 2) which is secreted into the haemolymph as a signal molecule (Kelly and Kavanagh 2011) and apolipophorin-3 (spot 8) which functions in the innate immune response (Gupta et al 2010). Spot 6, hypothetical protein YQE_03765 partial, was increased in abundance in larvae that received SBC3 and functions as a death domain protein with roles in apoptosis, immune defense, and immune signalling (Lahm et al 2003).…”
Section: Discussionmentioning
confidence: 99%